2010
DOI: 10.1002/piq.20089
|View full text |Cite
|
Sign up to set email alerts
|

Theory development and convergence of human resource fields: Implications for human performance technology

Abstract: This study examines major theory developments in human resource (HR) fields and discusses implications for human performance technology (HPT). Differentiated HR fields are converging to improve organizational performance through knowledge‐based innovations. Ruona and Gibson (2004) made a similar observation and analyzed the historical evolution and convergence of three HR‐related fields: human resource management (HRM), human resource development (HRD), and organization development (OD). A field left out in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Only recently have some HPT scholars produced a series of survey studies that provide an overview of the field. For instance, Cho and Yoon (2010) have suggested that HPT can learn from other theory development efforts in other HR fields.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only recently have some HPT scholars produced a series of survey studies that provide an overview of the field. For instance, Cho and Yoon (2010) have suggested that HPT can learn from other theory development efforts in other HR fields.…”
Section: Discussionmentioning
confidence: 99%
“…Although HPT has been growing and providing solutions for organizations, whether it has become as a full-fledged field is still questioned (Cho & Yoon, 2010). Many HPT researchers have made efforts to pinpoint the state of the field using traditional research methods such as content analysis (Klein, 2002), the Delphi technique (Huglin et al, 2007), and web-based survey (Pershing et al, 2008).…”
Section: Traditional Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SHRD alignment emphasizes the need for the HRD function to be proactively responsive to external environmental demands existing for the organization, including economic, regulatory, social, labor‐force, and technological change factors (Alagaraja & Shuck, ; Cho & Yoon, ; McGuire, Garavan, O'Donnell, & Watson, ; Werner & DeSimone, 2012). At the same time, SHRD alignment requires the HRD function to be clearly connected and responsive to internal environmental factors in the organization such as organizational culture, stakeholder involvement, reward structure, and job demands, using a systems approach (Guerra‐Lopez, ; McGuire et al, ; Werner & DeSimone, ).…”
Section: Shrd Alignment: An Overview Of the Literaturementioning
confidence: 99%
“…The main goal is to suggest how technologies should be conceptualized and implemented within an organization to improve the effectiveness of employees' learning, performance, and development. Although topics, such as talent management and HR planning can be seen as the domain of human resource management (HRM), HR and closely related fields (e.g., HRD, HRM, organizational development, human performance technology, and instructional technology) are converging to become strategic partners for leading organizational competitiveness through human learning and performance (Cho & Yoon, 2010;Ruona & Gibson, 2004). Components and practices of virtual learning and technologies were drawn from several related topics, in particular, the learning and performance architecture (Rosenberg, 2006); strategic blended learning (Yoon & Lim, 2007); a holistic view of informal learning (Marsick, 2009); and technologies for HRD (Benson, Johnson, & Kuchinke, 2002;Yoon, 2008).…”
Section: Introductionmentioning
confidence: 99%